Compêndio de Ciência da Religião - Antônio de Araújo, Alden (Mandrágora, 2024)
PASSOS, João Décio, e USARSKI, Frank (Orgs.): Compêndio de Ciência da Religião, São Paulo: Paulinas/Paulus, 2013, ISBN 978-85-356-3576-8, 702p.